2020
DOI: 10.1088/1742-6596/1477/4/042022
|View full text |Cite
|
Sign up to set email alerts
|

The Analysis of Mathematics Students’ Computational Thinking Ability at Universitas Siliwangi

Abstract: The rapid development of science and technology requires students to master various abilities and skills in order to compete globally. No exception students in mathematics education study programs. One of the abilities students must have is the ability to think computationally. Computational thinking ability is part of the problem-solving ability that is the ability of students to solve problems through decomposition skills, pattern recognition, algorithm thinking, abstraction and generalization of patterns to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Findings by Van Borkulo et al (2021) show that students who have CT skills can solve computational problems using GeoGebra. Sunendar et al (2020) also reported similar benefits because they can finally solve problems students encounter after being given CTrelated supplies. Related to the effectiveness of using internet quota.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Findings by Van Borkulo et al (2021) show that students who have CT skills can solve computational problems using GeoGebra. Sunendar et al (2020) also reported similar benefits because they can finally solve problems students encounter after being given CTrelated supplies. Related to the effectiveness of using internet quota.…”
Section: Discussionmentioning
confidence: 82%
“…Research results related to solving real problems encountered by students were reported by Sunendar et al (2020). This study analyzes the computational thinking abilities of students in Indonesia.…”
Section: Ct Helps Students Solve Real Problems They Encountermentioning
confidence: 99%
“…Maharani et al, 2021;S. Maharani, Kholid, et al, 2019;Sunendar et al, 2020), analysis of misconceptions based on CT test results (Masfuah & Fakhriyah, 2019), and analysis of CT abilities based on problem-solving processes in linear equation (Aminah, Leonardus, et al, 2022), algebra (S. , and geometry (Masfingatin & Maharani, 2019). Second, research that develops media to introduce and enhance students' CT.…”
Section: Discussionmentioning
confidence: 99%